Analysis of Clear Aligner Therapy Predictability for Mandibular Incisor Intrusion in Children and Adults - Christopher Burns; Abdul Basir Barmak; Robert Tarby; Dimitrios Michelogiannakis; Paul Emile Rossouw (Applied Sciences)
(1) The aim was to evaluate the predictability of treatment outcomes using clear aligner therapy (CAT) and ClinCheck Web 1.4 (Align Technology, Inc., San Jose, CA, USA) software in mandibular incisor intrusion in both children and adults with deep bite malocclusion. (2) This study included healthy children and adults with skeletal Class I or mild to moderate Class II/III malocclusions, mild to moderate dental crowding (<5 mm), and deep overbite (OB) who underwent CAT. Pre-treatment (T1) and post-treatment (T2) orthodontic treatment records were assessed and compared to initial planned ClinCheck movements. The cephalometric parameters evaluated included bodily intrusion (Centroid-C point), IMPA, L1-NB, and L1-A-Po. Clinical expression of CAT was compared to ClinCheck predictions using paired sample t-tests, and differences between growing and non-growing groups were assessed using a repeated measures ANOVA with Tukey post hoc analysis. (3) The sample included 48 patients (mean age 19.79 ± 11.78 years), including 18 adults (mean age 30.28 ± 13.79 years) and 30 children (mean age 13.5 ± 2.05 years). The predicted vertical mandibular incisor movement (intrusion) was significantly higher using ClinCheck (2.32 mm) compared to clinical treatment (0.22 mm). The angular movements of IMPA, L1-NB, and L1-APo were all significantly higher using ClinCheck (4.6°) compared to clinical expression of 0.79°, 0.55°, and 1.21°, respectively. There were no significant differences between children and adults with respect to vertical or angular tooth movements. (4) CAT and ClinCheck software significantly overpredicts orthodontic tooth movements related to mandibular incisor intrusion in both adults and children with no statistical difference between the groups.